Pemanfaatan Bahan Alami Menjadi Produk Tas Ecoprint Yang Bernilai Jual Di Banjar Indra Giri Dusun Sangiang - Komang Surya Putra Darmawan; I Nyoman Wijana; I Putu Gede Asnawa Dikta; I Komang Widya Purnamayasa (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2025)
This individual Community Service Program was carried out in Sangiang Hamlet with the main objective of enhancing the creativity of sisya pasraman through eco-friendly activities, specifically the creation of ecoprint bags. The program focused on utilizing leaves and local plants as primary materials to produce works with aesthetic, educational, and economic value. It also aimed to foster environmental awareness and instill an entrepreneurial spirit from an early age. A descriptive qualitative method was applied, involving observation, documentation, and hands-on practice. The program centered on ecoprint bag-making using pounding and steaming techniques, designed to actively engage the sisya, improve technical skills, and develop creative and innovative thinking. The resulting ecoprint products were marketed as an effort to introduce the potential of the local creative economy. The outcomes indicated that the sisya pasraman successfully transformed simple materials into marketable products, while also showing improvements in discipline, teamwork, and self-confidence. The ecoprint activity further provided new experiences in utilizing local plants as natural dyes and promoted the concept of sustainable green economy. Overall, the program effectively nurtured creative, independent, and environmentally conscious characters among the sisya, while making a tangible contribution to the development of the local creative economy.